👤

Transform f(x) = x² - 12 in the form f(x) = a (x - h) + k

Sagot :

Answer:

Our equation is in standard form to begin with: y=ax2+bx+c

We want to put it into vertex form: y=a(x-h)2+k

We can convert to vertex form by completing the square on the right hand side

36 is the value for 'c' that we found to make the right hand side a perfect square trinomial

Our perfect square trinomial factors into two identical binomials, (x+6)•(x+6)

The vertex of an equation in vertex form is (h,k), which for our equation is (-6,-4)

y=x2+12x+32 is in standard form

We want to get it into vertex form

To do this, we are going to use the method of completing the square

Standard form of a quadratic equation is y=ax2+bx+c, where 'a' is not 0

Vertex form of a quadratic equation is y=a(x-h)2+k, where (h,k) is the vertex of the quadratic function